2018
DOI: 10.1007/s00426-018-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulating proactive cognitive control by reward: differential anticipatory effects of performance-contingent and non-contingent rewards

Abstract: The present study investigated the influences of two different forms of reward presentation in modulating cognitive control. In three experiments, participants performed a flanker task for which one-third of trials were precued for a chance of obtaining a reward (reward trials). In Experiment 1, a reward was provided if participants made the correct response on reward trials, but a penalty was given if they made an incorrect response on these trials. The anticipation of this performance-contingent reward incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 58 publications
5
18
0
Order By: Relevance
“…In this case, the effect of rewards did not influence the inhibition performance (see similar findings in Michałowski et al, 2017;Paschke et al, 2015;Schevernels et al, 2015;and Shanahan et al, 2008). Furthermore, some studies have reported the presence of reward being detrimental to IC (Marini et al, 2015;Williams et al, 2018;Yamaguchi & Nishimura, 2019), possibly due to a break in attentional focus caused by reward stimuli (Wang et al, 2018). Finally, studies have examined whether the presence or magnitude of reward interacts with clinical diagnoses (e.g., attention-deficit hyperactivity disorder [ADHD], substance use disorder [SUD]); however, these effects are also equivocal (Charles-Walsh et al, 2016;Chung et al, 2011;Rosell-Negre et al, 2016).…”
Section: Introductionsupporting
confidence: 67%
“…In this case, the effect of rewards did not influence the inhibition performance (see similar findings in Michałowski et al, 2017;Paschke et al, 2015;Schevernels et al, 2015;and Shanahan et al, 2008). Furthermore, some studies have reported the presence of reward being detrimental to IC (Marini et al, 2015;Williams et al, 2018;Yamaguchi & Nishimura, 2019), possibly due to a break in attentional focus caused by reward stimuli (Wang et al, 2018). Finally, studies have examined whether the presence or magnitude of reward interacts with clinical diagnoses (e.g., attention-deficit hyperactivity disorder [ADHD], substance use disorder [SUD]); however, these effects are also equivocal (Charles-Walsh et al, 2016;Chung et al, 2011;Rosell-Negre et al, 2016).…”
Section: Introductionsupporting
confidence: 67%
“…Relatedly, inhibition of a dominant response tendency can also trigger stimulus devaluation (Wessel, O’Doherty, Berkebeile, Lindemann, & Aron, ), which corroborates a tight relationship between the evaluative and cognitive control processes. Furthermore, studies have shown that affective stimuli can modulate conflict adaptation, providing further evidence for a functional role of affect for control (Kuhbandner & Zehetleitner, ; Schuch & Koch, ; Schuch, Zweerings, Hirsch, & Koch, ; van Steenbergen, Band, & Hommel, , , ; but see Dignath, Janczyk, & Eder, ; Yamaguchi & Nishimura, , Exp. 2 & 3).…”
Section: Introductionmentioning
confidence: 87%
“…A central tenet of the DMC framework is that we shift to more effective, but more effortful, proactive control only when it is worthwhile to do so (see Botvinick & Braver, 2015, for a review). Reward is one incentive that is known to motivate a shift to proactive control in emotionally neutral contexts (Chiew & Braver, 2013Fröber & Dreisbach, 2014Hefer & Dreisbach, 2016;Locke & Braver, 2008;Padmala & Pessoa, 2011;Yamaguchi & Nishimura, 2018). This proactive shift is thought to be implemented via connections between reward-processing areas (such as the ventral striatum and orbitofrontal cortex) and cognitive control regions (such as the anterior cingulate cortex and dorsolateral prefrontal cortex; Botvinick & Braver, 2015;Pessoa, 2009;Pessoa & Engelmann, 2010).…”
mentioning
confidence: 99%